2012
DOI: 10.1007/s00393-012-1076-7
|View full text |Cite
|
Sign up to set email alerts
|

Synovialitis vom arthrofibrotischen Typ

Abstract: After rheumatologic conservative medical therapy has been exhausted in degenerative and inflammatory joint diseases, arthroplastic operations are an important option to restore quality of life. Endoprosthesis-associated arthrofibrosis is a severe fibrosing disease of the synovial membrane after endoprosthetic operations. Neither the morphological substrate nor histopathological criteria have been described. The aim was to describe the histopathological substrate of arthrofibrosis and to define histological and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Although the predicted incidence of primary arthrofibrosis after knee replacement is 10%, its pathogenesis is mostly unclear and no diagnostic marker has been described 4 . Until today, the diagnosis is based on histopathological findings and clinical symptoms such as loss of motion 5 6 . Treatment of arthrofibrosis is challenging and several therapeutic strategies have been discussed 4 7 .…”
mentioning
confidence: 99%
“…Although the predicted incidence of primary arthrofibrosis after knee replacement is 10%, its pathogenesis is mostly unclear and no diagnostic marker has been described 4 . Until today, the diagnosis is based on histopathological findings and clinical symptoms such as loss of motion 5 6 . Treatment of arthrofibrosis is challenging and several therapeutic strategies have been discussed 4 7 .…”
mentioning
confidence: 99%
“…There are several important starting points in the etiology of AF. Activation of the fibroblast and myofibroblast is an important aspect with increased production of collagen type VI [ 11 ], alpha-smooth muscle protein [ 12 ], β-catenin [ 13 ], reactive oxygen and nitrogen species (also in macrophages and neutrophils) [ 14 ], and bone morphogenic protein type II [ 15 ]. The proinflammatory cytokine interleukin (IL)-1β might also play a role since injection of anakinra, the IL-1 receptor antagonist, was effective in an open study in AF patients [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, sonographic studies in humans demonstrated increased neovascularization in the synovial tissue and infrapatellar fat pad (Hoffa) [ 4 ]. All these factors relevant for a profibrotic process demonstrate a continuous smoldering low-grade inflammation characterized as a new type of synovialitis [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation